2019
DOI: 10.1016/j.ctim.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Weight control and physical exercise in people with multiple sclerosis: Current knowledge and future perspectives

Abstract: Highlights 3 weight loss in people MS is needed. The most comprehensive weight management guidelines are outlined in the American College of Sports Medicine Position Statement, which recommends between 150-250 minutes per week of moderate-intensity physical activity for preventing weight gain, and between 225-420 minutes per week of moderate-intensity physical activity for weight loss. These recommendations seem applicable for people with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 71 publications
(90 reference statements)
0
16
0
8
Order By: Relevance
“…We observed comparable time-courses of EAE in terms of neurological signs and body weight. Others also observed a notable weight loss of fat and muscle mass in EAE mice (Bernardes et al, 2016), while both cachexia (Kamalian et al, 1975;Van Waesberghe et al, 1999) and weight gain (Mokhtarzade et al, 2019) were reported in MS. More recent studies also indicate that hypothalamic inflammation precedes both involuntary weight loss and obesity [ (Clarke, 2010) and references within]. Our experiments also indicate that the phase in loss of body weight coincides with hypothalamic inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…We observed comparable time-courses of EAE in terms of neurological signs and body weight. Others also observed a notable weight loss of fat and muscle mass in EAE mice (Bernardes et al, 2016), while both cachexia (Kamalian et al, 1975;Van Waesberghe et al, 1999) and weight gain (Mokhtarzade et al, 2019) were reported in MS. More recent studies also indicate that hypothalamic inflammation precedes both involuntary weight loss and obesity [ (Clarke, 2010) and references within]. Our experiments also indicate that the phase in loss of body weight coincides with hypothalamic inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, there is evidence suggesting that PwMS who perform more PA have a lower BMI and are less likely to be obese [18,19]. This discrepancy may be explained by the parameters used to assess obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss may be associated with a more favorable progression of disease for patients with obesity and MS. Although nonoperative weight loss regimens may be beneficial, the chance of reaching long-term significant weight loss appears to be small [28]. In the present study, metabolic surgery (with gastric bypass or sleeve gastrectomy) showed weight loss in line with patients without MS and also showed significant improvements in both obesity-specific and generic HRQoL.…”
Section: Discussionmentioning
confidence: 47%